Remembering Sir William Osler 100 years after his death: what can we learn from his legacy? - Becker, Robert E. (2015)
William Osler is a physician par excellence in the history of medicine. As father of modern Hippocratic medicine moved the foundations of medical education nineteenth century classrooms at the bedside of patients (Figure) introduced the routine use of laboratory and autopsy as part of education and medical practice and it brought schooling, humility and humanity in the doctor-patient relationship. He was loved by those who knew and respected by his generation and those that followed. It provided patient care caring first of all by the same person. Osler still receives praise, with justice merecidos- to advance the seat of science, humanities and professionalism in medicine (see the references section). Osler is less recognized for error control, variational biology, the scientific method and humanism-issues problematic for modern medicine.